PENGARUH KUALITAS PELAYANAN BOARDING GATE TERHADAP KEPUASAN PENUMPANG DI MASKAPAI CITILINK BANDAR UDARA YOGYAKARTA INTERNASIONAL - Rahmat Narwan Fadli; Nuning Agustina Ambarsari,S.E.,M.M (Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
Service quality is built on a comparison of two main factors, namely customer perceptions of the real service they receive with the service they actually expect or want. If the reality is more than expected, then the service can be said to be of high quality, whereas if the reality is less than expected, then the service can be said to be of poor quality. And if the reality is the same as the expectation, then the service can be said to be satisfactory. This research is a quantitative research, quantitative research is a research method based on the philosophy of potivism, used to examine certain populations or samples. The data sources used are primary data and secondary data, primary data obtained from Citilink airline passengers at Yogyakarta International Airport who were asked for responses through questionnaires given about service quality variables and passenger satisfaction variables. Based on the data analysis, it was concluded that the effect of the variable quality of boarding gate services significantly on the variable of passenger satisfaction. And the contribution between the variables of service quality boarding gate (X) contributed 0.863 or 86.3% to passenger satisfaction on the Citilink airline at Yogyakarta International Airport, the remaining 13.7% was influenced by other factors not included in this study. Keywords: Quality of Service, Boarding Gate, Passenger Satisfaction and Citilink Airlines.